Effect of ultrasound thawing, vacuum thawing, and microwave thawing on gelling properties of protein from porcine longissimus dorsi - Wang, Bo; Du, Xin; Kong, Baohua; Liu, Qian; Li, Fangfei; Pan, Nan; Xia, Xiufang; Zhang, Dongjie (Ultrasonics sonochemistry, 2020)
•Effect of three new thawing methods on gel property of protein was analyzed.•Change in MP gel surface morphology was observed by atomic force microscopy.•Effect of ultrasound and vacuum thawing on gel property was lower than others.•Destruction in gel property of microwave thawing was obvious. Effect of new thawing methods (ultrasound thawing (UT), vacuum thawing, (VT), microwave thawing (MT)) on gelling properties of myofibrillar protein (MP) from porcine longissimus dorsi was investigated, compared with traditional thawing methods (water immersion thawing, (WT)) and fresh meat (FM). The results showed that a decrease in MP gelling properties of all thawing samples was observed. The increase in roughness of MP gel from all thawing samples explained that the flatter, smoother, and denser surface morphology of that from FM samples was destroyed based on the observation by atomic force microscopy. There was significant difference (P < 0.05) in all gel indicators (particle size, turbidity, whiteness, water-holding capacity (WHC), moisture distribution, rheological characteristics, surface morphology) of MP from MT samples and there was insignificant difference (P > 0.05) in turbidity, whiteness, WHC of MP from VT samples compared with that from FM samples. There was insignificant difference (P > 0.05) in gel properties between UT and VT. The effect of UT and VT (new thawing methods) on MP gelling properties was significantly lower (P < 0.05) than that of WT (traditional thawing methods), and the effect of that from MT was obviously compared with other thawing methods.